Evaluation of effects of resveratrol on brain nitric oxide and energy metabolism in metabolic syndrome model - Ozan, Gonca; Bircan, Filiz Sezen; Pasaoglu, Ozge Tugce; Topal, Turgut; Turkozkan, Nurten (Derman Medical Publ, 2017)
Aim: A high fructose diet promotes nitrosative stress that makes the brain susceptible to dysfunction and neurodegeneration. The aim of this study was to examine the possible resveratrol effects on brain nitrosative stress and energy balance in the fructose-mediated metabolic syndrome (MetS) model. Material and Method: Adult male Sprague-Dawley rats were separated into four groups (n-8 in each group): control, fructose, resveratrol and fructose plus resveratrol. MetS was induced by fructose solution 20% in tap water, and resveratrol was applied at the dose of 10mg/kg daily by oral gavage. Systolic blood pressures (SBP) were measured by the tail-cuff method. After the experimental period of eight weeks, serum triglycerides, glucose, insulin and total brain tissue ATP/ADP ratio, nitric oxide (NOx) and 3-nitrotyrosine (3-NT) levels were measured. Also tissue endothelial and inducible nitric oxide synthase (eNOS and iNOS) protein levels were determined by western blotting. Results: Fructose increased SBP, serum triglycerides, insulin levels and induced insulin resistance significantly compared to the control group. In comparison with control group, fructose did not cause significant differences in tissue ATP/ADP ratio, 3-NT and NOx levels. While resveratrol had no effect on NOx and 3-NT levels, it caused a decrease in the ATP/ADP ratio in both the resveratrol and resveratrol plus fructose groups. iNOS and eNOS proteins were not detected in any of the groups. Discussion: These results indicate that a high fructose diet for eight weeks did not influence NO production, energy metabolism or protein nitration in rat brain tissues. Nevertheless resveratrol acted as a pro-oxidant at that dose when administered with fructose and alone.
Keywords: Fructose; Resveratrol; ATP; Brain